Synthesis and Characterization of Ni2O3 as a Phase of Nickel Oxide Nanomaterial - Hussein, Nagham Ali; Ali, Nathera Abass (Iraqi Journal of Science, 2022)
Ni2O3 nanomaterial, a phase of nickel oxide, is synthesized by a simple chemical process. The pure raw materials used in the present process were nickel chloride hexahydrate NiCl2.6H2O and potassium hydroxide KOH by utilizing temperature at 250 oC for 2 hour. The structural, morphological and optical properties of the synthesized specimens of Ni2O3 were investigated employing diverse techniques such as XRD, AFM, SEM and UV-Vis, respectively. The XRD technique confirms the presence of Ni2O3 nanomaterial with crystal size of 57.083 nm which indexing to the (2θ) of 31.82; this results revealed the Ni2O3 was a phase of nickel oxide with Nano structure. The synthesized Ni2O3 will be useful in manufacturng electrodes materials for fuel cell and production catalytic materials for electrolysis cell.